STUDI ANALISA HARGA SATUAN PEKERJAAN BETON DENGAN METODE BOW, SNI DAN LAPANGAN PADA PROYEK IRIGASI BATANG ANAI II - Nasrul Nasrul (Jurnal Momentum ISSN 1693-752X)
To improve the efficiency and effectiveness of activities in the construction field, we need a basic means of calculating the unit cost i.e. Construction Cost Analysis. The Construction Cost Analysis, known among, are BOW analysis, SNI and Field/Contractor. To get the expected unit price, the three methods are compared to provide an efficient estimated cost , to plan and to control resources such as material, labor, equipment and time. In analyzing the unit price of reinforced concrete work in Batang Anai Irrigation II project, to perform the unit price, data of images bestek, RAB offers contractors, RKS, a list of materials and wage rates in the study area are needed. From the calculation of unit price analysis is found the unit price comparisons of materials, wages and employment of reinforced concrete between SNI method, BOW and field. The dominant component that is become an equation in the calculation of the unit price is in determining the unit price index of the material which is based on the number of materials used per unit of work and labor index work which is based on daily wages and employment and labor productivity in completing the work per unit, while the dominant component of distinction is the wage unit price. Results of calculation of unit price for the concrete work are Rp. 5,610,812.294 for BOW method, Rp 3,704,145.996 for SNI and Rp 4,197,553.963 for Field Method, where the the largest unit price is seen in the unit prices of materials and wages concrete. so it can be concluded that the components of reinforced concrete work that is most significantly affect the unit price is concrete work and the most effective method is the SNI method.